Linguistic Patterns of Slang Usage in Adolescent Communication - Nur R, Alyssa; Susanti, Novi (LPPM Universitas Duta Bangsa Surakarta, 2023)
Language functions not only as a means of communication but also as a medium for social integration and adaptation in a linguistically diverse society. Slang represents a form of language commonly used by teenagers, often characterized by a sense of exclusivity and informality. These expressions are typically brief, trendy, and easy to remember. This study aims to identify the types of slang frequently used by Indonesian teenagers, uncover their meanings, and explore the reasons behind their use. Employing a descriptive qualitative approach, the research relies on document analysis with listening and note-taking techniques. Findings indicate that slang is widely adopted among teenagers due to its simplicity, memorability, and ability to foster a relaxed, familiar atmosphere within peer interactions